Que nous dit l’offre Airbnb sur l’évolution des territoires touristiques ? Le cas de La Rochelle/Île de Ré - Claire Bouquet; Luc Vacher; Didier Vye (M@ppemonde)
Tourist accommodations have been deeply affected by the growing success of collaborative platforms, particularly AirBnB. As such, it is vital to scientifically measure this phenomenon. This article will look at the benefits and limits of spatial data mining methods regarding these new types of accommodations. We will then examine the meaning of such data when compared to conventional accommodations. Finally, based on a case study including two French tourist destinations (La Rochelle/Ile de Ré), we will analyse the spatial distribution of supply in order to evaluate current changes within tourist locations.